Coprophagy in moose ... - Spitzer, Robert; Åström, Cecila; Felton, Annika; Eriksson, Monika; Meisingset, Erling L.; Solberg, Erling J.; Rolandsen, Christer M. (Dryad, 2023)
Coprophagy, the eating of feces, has been documented in a wide range of species but appears to be rare or difficult to detect in deer (Cervidae). Here, we report the first observation of coprophagy in moose Alces alces, which was recorded using camera collars on free-ranging moose in Norway. The footage shows an instance of allocoprophagy by an adult female moose in spring (May). We summarize the current knowledge about coprophagy in deer and briefly discuss potential drivers and possible implications for disease transmission. Further research is needed to determine if coprophagy occurs frequently in moose and whether this behavior is positive (e.g., increased intake of nutrients) or negative (increased infection by parasites or pathogens). ... : The video footage showing allocoprophagy in a female moose was recorded using a video collar (VERTEX Plus, Vectronic Aerospace GmbH, Germany) on 20th of May, 2018 at 04:30 PM in the county of Trøndelag (N 63° 15.942’ E 11° 51.273’). ...